2008
DOI: 10.1124/dmd.108.024646
|View full text |Cite
|
Sign up to set email alerts
|

An Unexpected Synergist Role of P-Glycoprotein and Breast Cancer Resistance Protein on the Central Nervous System Penetration of the Tyrosine Kinase Inhibitor Lapatinib (N-{3-Chloro-4-[(3-fluorobenzyl)oxy]phenyl}-6-[5-({[2-(methylsulfonyl)ethyl]amino}methyl)-2-furyl]-4-quinazolinamine; GW572016): TABLE 1

Abstract: ABSTRACT:Lapatinib is a tyrosine kinase inhibitor approved for use in combination with capecitabine to treat advanced or metastatic breast cancers overexpressing human epidermal receptor 2 (ErbB2). This work investigated the role of P-glycoprotein (Pgp; the protein from the Mdr1a/b gene) and breast cancer resistance protein (Bcrp; the protein from the Bcrp1 gene) in modulating the central nervous system penetration of lapatinib at steady-state conditions in FVBn mice (wild-type), Mdr1a/b(؊/؊), Bcrp1(؊/؊), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
204
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(227 citation statements)
references
References 14 publications
22
204
1
Order By: Relevance
“…Similar results as for dasatinib on the dominant role of P-gp at the BBB were found for the TKIs imatinib and lapatinib, which are good substrates for both P-gp and ABCG2 (6,34). Deficiency of Abcg2 alone did not lead to an increased brain accumulation, whereas single P-gp knockout mice had higher brain levels than WT mice.…”
Section: Discussionsupporting
confidence: 70%
“…Similar results as for dasatinib on the dominant role of P-gp at the BBB were found for the TKIs imatinib and lapatinib, which are good substrates for both P-gp and ABCG2 (6,34). Deficiency of Abcg2 alone did not lead to an increased brain accumulation, whereas single P-gp knockout mice had higher brain levels than WT mice.…”
Section: Discussionsupporting
confidence: 70%
“…These results showed no effect of abcg2 2/2 , a marked increase in brain exposure in abcb1a/b 2/2 , and an even greater increase in the triple knockout. The ability of P-gp and bcrp to work together to limit brain disposition has also been described for lapatinib and dasatinib (Chen et al, 2009;Polli et al, 2009). The results of Poller et al (2011) suggested that the mouse mdr1 limits the brain distribution of axitinib, with the role of bcrp being unclear.…”
Section: Transporters For Axitinibmentioning
confidence: 99%
“…In particular, the drug efflux transporters expressed at the BBB play a very important role in limiting the brain penetration of a wide variety of compounds including frequently used chemotherapeutics and novel targeted agents. Two well-established drug efflux transporters, ABCB1 (P-glycoprotein, P-gp, MDR1) and ABCG2 (Breast Cancer Resistance Protein, BCRP), are abundantly expressed in the human and murine BBB and restrict most newly developed kinase inhibitors such as erlotinib, lapatinib, and palbociclib (15)(16)(17). As a consequence, the usefulness of such agents in glioblastoma treatment might be attenuated by an inadequate brain penetration.…”
Section: Introductionmentioning
confidence: 99%